2022
DOI: 10.3390/clockssleep4040046
|View full text |Cite
|
Sign up to set email alerts
|

Associations among Alcohol Drinking, Smoking, and Nonrestorative Sleep: A Population-Based Study in Japan

Abstract: Nonrestorative sleep (NRS) is a common sleep disorder. It is associated with several unhealthy lifestyle factors, such as skipping breakfast and lack of exercise. However, the associations between alcohol drinking, smoking, and NRS are unclear. This study examined the prevalence of NRS within the Japanese general population and the relationships among alcohol drinking, smoking, and NRS. We analyzed an anonymized dataset from a 2013 nationwide population survey (35,717 men and 39,911 women). NRS was assessed th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…In addition, we could not collect information from younger individuals in this study. The prevalence of NRS in younger populations was equivalent to that in the age group of 50–59 years in Japan [ 42 ], and long-term NRS exposure may be a risk factor for premature MetS. Future prospective studies should investigate the NRS status of younger populations.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, we could not collect information from younger individuals in this study. The prevalence of NRS in younger populations was equivalent to that in the age group of 50–59 years in Japan [ 42 ], and long-term NRS exposure may be a risk factor for premature MetS. Future prospective studies should investigate the NRS status of younger populations.…”
Section: Discussionmentioning
confidence: 99%
“…This indicates that non-smoking and diabetic menopausal women who sleep less have higher depression scores. A meta-analysis found that smokers are 47% more likely than non-smokers to experience sleep problems ( 54 ). Inadequate sleep is strongly associated with smoking ( 55 ).…”
Section: Discussionmentioning
confidence: 99%
“…Participants with smoking habits were categorized as non-regular smokers (including never, quit, and occasionally) and regular smokers (including fewer than 10 cigarettes, 11–20 cigarettes, and 23 or more cigarettes daily). Participants with alcohol consumption were categorized as habitual drinkers (40 g or more alcohol consumption per day) and occasional/non-drinkers (40 g or less alcohol consumption per day), according to a previous study that suggested that alcohol consumption of less than 40 g per day might not affect sleep [ 21 , 22 ]. We dichotomized the participants depending on their exercise habits: regular exercisers (120 min or more a week) and non-regular exercisers (119 min or less a week), according to a previous study, which showed that exercising for 150 min or more per week decreases mortality [ 23 ].…”
Section: Methodsmentioning
confidence: 99%